2021
DOI: 10.52633/jms.v3i2.65
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Factors Affecting Purchase Intention of Counterfeit Products

Abstract: This research paper is based on investigating the factors affecting the purchasing decision of counterfeit product consumers in the city of Karachi. The study was conducted through convenient sampling by developing a questionnaire based on behavioural as well as demographic questions. The questionnaire was circulated through the social mediums and feedback was collected to carry out statistical tests for the conclusion purpose. A total of 87 responses were received through the survey questionnaire. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…This finding is in line with the Theory of Cognitive Dissonance which states that individuals seek consistency in their beliefs, behaviors and attitudes; if they experience inconsistency a state of dissonance occurs (Festinger, 1957). In the context of religiosity and luxury consumption, if an individual seeks luxury purchases and his religious beliefs hinder materialism and discourage excessive consumption, then a state of cognitive dissonance exists (Ashraf et al, 2017). Hasan and Nasreen (2012) found that a state of dissonance or stress is usually more JIMA 14,7 dominating in consumers' decisions involving the purchase of luxury products when compared to other products.…”
Section: Religiosity and Luxury Consumptionsupporting
confidence: 82%
See 4 more Smart Citations
“…This finding is in line with the Theory of Cognitive Dissonance which states that individuals seek consistency in their beliefs, behaviors and attitudes; if they experience inconsistency a state of dissonance occurs (Festinger, 1957). In the context of religiosity and luxury consumption, if an individual seeks luxury purchases and his religious beliefs hinder materialism and discourage excessive consumption, then a state of cognitive dissonance exists (Ashraf et al, 2017). Hasan and Nasreen (2012) found that a state of dissonance or stress is usually more JIMA 14,7 dominating in consumers' decisions involving the purchase of luxury products when compared to other products.…”
Section: Religiosity and Luxury Consumptionsupporting
confidence: 82%
“…Religion was found to have a negative effect on consumer's attitude toward luxury brands consumption (Dekhil et al, 2017). Moreover, according to Ashraf et al (2017) individuals with higher religiosity levels are more discouraged toward materialistic ownerships. It has been claimed that a person with strong commitment to religion may experience psychological self-guilt or stress when seeking material possessions (Burroughs and Rindfleisch, 2002).…”
Section: Religiosity and Luxury Consumptionmentioning
confidence: 97%
See 3 more Smart Citations